(3JShjb GdNOeGJ GdeGdjIs - (3KGeQ(B, (3GdHcQjs ((3YeGf(B:s (3GKQGA ddfTQ h GdJhRjY(B,s, 2008)
(3jVe eONd aj GdJShjb, bSe GdJShjb aj GdTQcGJ GdeGdjI, eONd aj JShjb GdNOeGJ GdeGdjI, GdHjFI GdJShjbjI GdCQOfjI ddNOeGJ GdeGdjI, Sdhc GdeSJgdc, fXGe GdeYdheGJ GdJShjbj GdeGdj, GSJQGJjLjI JShjb GdNOeGJ GdeGdjI, GdefJL (B((3GdNOeI(B) (3GdeGdjI GdJhRjY ddNOeGJ GdeGdjI, GdGJUGdGJ GdJShjbjI(B((3GdJQhjL(B) (3ddNOeGJ GdeGdjI, JSjjQ GdNOeGJ GdeGdjIs
Keywords: (3GdJShjbs; (3GdJehjds